2010
DOI: 10.1673/031.010.12601
|View full text |Cite
|
Sign up to set email alerts
|

Ant mimicry by an aphid parasitoid, Lysiphlebus fabarum

Abstract: In Iran, Lysiphlebus fabarum (Marshall) (Hymenoptera: Braconidae: Aphidiinae) is a uniparental parasitoid of the black bean aphid, Aphis fabae Scopoli (Hemiptera: Aphididae), that possesses various highly evolved adaptations for foraging within ant-tended aphid colonies. Direct observations and video recordings were used to analyze the behavior of individual females foraging for A. fabae on bean leaf disks in open arenas in the laboratory. Females exploited aphids as hosts and as a source of food, allocating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Similarly, Gerling et al (1990) showed that Aphelinus asychis (Walker) preferred to attack pea aphids, Acyrthosiphon pisum (Harris), from an anterior or posterior orientation, thus reducing the effectiveness of host defensive behavior. As A. fabae feed with their stylets embedded quite deeply in plant tissues, they are unable to withdraw them quickly and tend to resort to rotating their body around their point of attachment rather than releasing the plant when attacked (Rasekh et al, 2010b). Escape appeared to be the least frequent of defensive responses (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Gerling et al (1990) showed that Aphelinus asychis (Walker) preferred to attack pea aphids, Acyrthosiphon pisum (Harris), from an anterior or posterior orientation, thus reducing the effectiveness of host defensive behavior. As A. fabae feed with their stylets embedded quite deeply in plant tissues, they are unable to withdraw them quickly and tend to resort to rotating their body around their point of attachment rather than releasing the plant when attacked (Rasekh et al, 2010b). Escape appeared to be the least frequent of defensive responses (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Cornicle secretion by aphids can be an effective defense against attack by parasitoids (Edwards, 1966;Rasekh et al, 2010b;Hopkinson et al, 2013) and predators (Acar et al, 2001;Butler & O'Neil, 2006). As cornicle droplets contain the alarm pheromone E-b-farnesene, they may yield inclusive fitness benefits by warning related conspecifics of an impending attack, even if they fail to protect the emitting individual (Wu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second group was kept in plastic cylinders for 72 h (old mothers) and then randomly introduced to synchronous cohorts of black bean aphid as above. The median longevity of L. fabarum females feeding on diluted honey was 4.5 days (Rasekh et al, 2010), so 72-h mothers used in this experiment were considered as old mothers. These test procedures were repeated in exactly the same manner for wasps that emerged from first (small mothers) and second (large mothers) instars.…”
Section: Mothersmentioning
confidence: 99%